Teaching Reading Comprehension in Community Schools: Challenges and Strategies (Siddhajyoti Interdisciplinary Journal, 2026)
This article presents the views of secondary level English language teachers about their experiences of teaching reading comprehension in community schools. The main purpose of this study is to explore the difficulties in teaching reading comprehension and teaching strategies used by teachers to address these difficulties. I used the interpretive paradigm of research, in which the four teachers from four schools were asked to share their personal experiences in teaching reading comprehension. The main tool utilized in this study was a set of interview guidelines for teachers, under which they were asked to narrate their real-life experiences in order to expose their perception and experiences of teaching reading comprehension at secondary level in community schools.  The findings show that the students had problems with vocabulary, lack of background knowledge of the text in the readers, problems with inference, and difficulty in understanding the technical texts. The teachers addressed these problems through teaching vocabulary, questioning, applying co-operating reading strategy and explaining the text in simple language. The results from this study can be applied to provide insights for the teachers and teacher educators to improve the existing problems in teaching reading comprehension.